Impact of Monetary Policy on Bank’s Profitability: A Study on Listed Commercial Banks in Bangladesh - Hoque, Md. Ariful; Ahmad, Afzal; Chowdhury, Mustafa Manir; Shahidullah, Mohammad (International Journal of Accounting & Finance Review, 2020)
Monetary policy is the policy by which the government of a country control supplies of money in an economy which is announced by the central bank for every six months. Central Bank carries out monetary policy by the banking system of a country. Central Bank uses Bank rate; Cash reserve ratio and open market operation to control the availability of funds in an economy. Within these three instruments, the cash reserve ratio is directly linked to the commercial bank’s profitability. Every commercial bank maintains a cash reserve ratio against their demand & time deposits. Being changes in the cash reserve ratio banks profit level may increase or decrease. The prime intention here is to show the impact of monetary policy, especially Cash Reserve Ratio on the commercial bank’s profitability. This study covers only listed commercial banks in Bangladesh. As sample researcher purposively selected 15 listed commercial banks that have available information. Results revealed that CRR negatively related to Return On Assets (-0.1133), Return On Equity (-0.0577) as well as Return On Investment (-0.0504). This means the bank’s profitability declined due to the increase in cash reserve ratio (CRR). Again regression analysis outlined that the cash reserve ratio negatively impacts on the profitability of studied commercial banks in Bangladesh, which is statistically significant at the 10% level. Researchers proposed that Bangladeshi commercial banks will design their profitability plan by considering monetary policy tools, particularly the Cash reserve ratio.